Carl Menger's Contribution to Capital Theory - Eduard Braun (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2013)
The common interpretation of Carl Menger's take on capital theory rests upon a few sentences in his Principles of Economics. His later monograph on the topic, Zur Theorie des Kapitals (A contribution to the theory of capital), is more or less ignored, although it must be seen as a recantation of his earlier views. As it becomes clear in this work, Menger would have opposed all attempts to define capital as a heterogeneous structure of higher-order goods – a definition that is associated with his name today. In his opinion capital is a homogeneous concept stemming from accounting practices. The debate about Menger's view on capital does not only concern terminological points, but involves the subject matter of capital theory. A theory of capital based on Menger's later view would concentrate on the way the market economy is organized and not on technical characteristics of a multi-stage production process.
Keywords: B1; B53; E22; 330; Carl Menger; Capital Theory; History of Economic Thought